Does the Starting of Clozapine Influence Coprescription of Other Medications?: A Study From India. Issue 2 (March 2021) - Grover, Sandeep; Naskar, Chandrima; Chakrabarti, Subho
Abstract: Purpose/Background: Little is understood about the prescription load before and after the starting of clozapine. Accordingly, this study aimed to evaluate the medication load of patients receiving clozapine, just before starting clozapine and after being on clozapine for at least 1 year. Additionally, the impact of clozapine on severity of illness was evaluated. Methods/Procedures: Two hundred seventy-seven outpatients receiving clozapine were prospectively evaluated for their prescription after at least 1 year of starting clozapine. Additionally, these patients were assessed on the Clinical Global Impression-Improvement scale to evaluate the overall clinical benefit with clozapine. Findings/Results: They had been receiving clozapine for 6.55 (SD, 4.8; range, 1–24; median, 5) years at the time of assessment. At the start of clozapine, more than one third of the patients were receiving 2 antipsychotics. A small proportion was receiving other psychotropics, such as antidepressants, mood stabilizers, and benzodiazepines. After being on clozapine for 1 year, there was a significant reduction in the number of patients receiving two antipsychotic medications ( P < 0.001), number of patients receiving antidepressants (if amitriptyline was left out), benzodiazepine ( P < 0.001), and anticholinergic medications ( P < 0.001). Further, there was a reduction in the mean chlorpromazine equivalent of antipsychotics ( P < 0.001) and the total number of medications received by the patients ( P < 0.001). However, there was an increase in the prescription rates of antihypertensive drugs ( P = 0.03), anti-diabetic medications ( P < 0.01), and anti-dyslipidemic medications. At follow-up, there was a significant improvement in symptoms as assessed by Clinical Global Impression-Improvement scale. Implications/Conclusions: This study suggests that long-term use of clozapine is associated with substantial improvement in symptoms with a reduction in the medication load.